Pesantren as the Identity of Islamic and Cultural Education in West Java - Lukman Hakim (STAI Hubbulwathan Duri, 2023)
In West Java, religion and culture are inseparable, with each influencing the other. Pesantren, dominant Islamic educational institutions, emphasize religious teachings that impact local culture. This study seeks to examine the role of Islamic boarding schools as the embodiment of Islamic and cultural education in West Java. This study employs a descriptive qualitative research method. This study uncovers the significance of Islamic boarding school complexes in Indonesian culture and education. Islamic boarding schools have significantly contributed to the spread of Islamic knowledge and the development of cultural values, even though they may not overtly state their educational objectives. This study emphasises the incorporation of religious knowledge and general information in contemporary Islamic boarding schools, underscoring the significance of Islamic and global education. In addition, this research emphasizes the role of cultural maintenance and Islamic boarding school modeling in forming ethical and moral values, which contribute to the nation's cultural richness. The implication of this research is that education in pesantren should continue to integrate religious and general education while preserving cultural values to serve as a means for shaping a strong and relevant cultural identity within Indonesian society.